Online Clinical Teacher Preparation Programs in Special Education: Perspectives and Critical Components. Issue 4 (December 2019) - Ottley, Jennifer R.; Coogle, Christan Grygas; Pigman, Jon Ryan; Sturgeon, Doug; Helfrich, Sara
Online special educator preparation programs are growing in prevalence and popularity. Yet, implementing a clinical model of special educator preparation within online programs can be challenging. In this study, we explored the perspectives of the clinical model from a distance for school-based teacher educators and administrators. We conducted a survey followed by focus group interviews to identify perspectives regarding the clinical model from a distance approach and the components of a distance preparation program perceived to be critical for effective clinical practice. School-based teacher educators and administrators had favorable views of the clinical model (including clinical coaching) from a distance, indicating both feasibility and acceptability. Many perceived technology-related challenges were malleable aspects of online preparation programs that university- and school-based teacher educators can plan for in the implementation of their online program and clinical practice from a distance.